Factors Influencing The Incident of Stunting at The Sagerat Public Health Center, Bitung City - Anik Sri Purwanti; Firda Firliana Karim (International Journal of Medicine and Health, 2025)
Background: Stunting remains a major public health concern in Indonesia, affecting children’s growth, development, and long-term health outcomes (Sari, 2020). Early childhood stunting can lead to cognitive delays, poor school performance, reduced productivity in adulthood, and increased risk of chronic diseases (Hapsari & Wulandari, 2019). Understanding the interaction of demographic, socioeconomic, and health-related factors is essential to reduce stunting prevalence and improve child health outcomes (Yuliani, 2019). Objective: This study aimed to analyze the factors influencing the incidence of stunting among children attending the Sagerat Public Health Center in Bitung City. Methods: A quantitative, observational study with a cross-sectional design was conducted. Thirty children were selected using purposive sampling based on inclusion criteria such as age under five years and available anthropometric data. The Wilcoxon signed-rank test was applied to examine the relationship between these factors and stunting incidence, with a significance level set at p < 0.05. Results: The analysis showed that 30 children (100%) in the study were at risk of stunting based on height-for-age measurements, with 20 children (90%) confirmed as stunted and 10 children (10%) having normal height. These results suggest that maternal education, socioeconomic status, nutrition, and access to healthcare are strongly associated with stunting in this population. Conclusion: Factors such as maternal education, socioeconomic status, dietary intake, and access to healthcare significantly influence the incidence of stunting among children at the Sagerat Public Health Center. Comprehensive community-based programs are recommended to reduce stunting prevalence and improve long-term health outcomes for children.